FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (Studi kasus pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Periode 2011 – 2014) - Mukhlan Khariry; Meina Wulansari Yusniar (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
This study aimed to analyze and test the effects of firm size, tangible assets, profitability, asset growth, sales growth and financial risks to the capital structure of the companies listed on the Indonesia Stock Exchange period 20112014. Methods used in this research was quantitative method using manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the period of 20112014 as the research population. The samples of 54 companies were selected by using purposive sampling method. The study hypothesis was tested by multiple linear regression which have fulfilled classical assumption test. The results showed that firm size (X1), asset growth (X4), and financial risks (X6) had significant influence with the positive directional effect towards the capital structure. Profitability factor (X3) had significant influence with the negative directional effect towards the capital structure. Meanwhile, the factors of tangible asset (X2) and sales growth (X5) had no significant effect towards the capital structure